Diversifying Quranic Revision Methods Using Gamification-based Teaching Material For Tahfiz Education - Abd Muhaimin Ahmad; Azman Ab. Rahman; Muhammad Hafiz Saleh; Zainora Daud (Institute of Advanced Engineering and Science (IAE, 2024)
Indexed by Scopus